Gaya Desain Minimalist UI/UX Website Senusa Basketball di Tangerang Selatan - Umeir Ilyasa Asshidiq; Nuryadi Nuryadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia hosted the 2023 FIBA Basketball World Cup (FBWC), which encourages the development of basketball clubs in the country, including Senusa Basketball Club in South Tangerang. Despite its achievements, the club does not have an effective means of communication, which hinders the dissemination of information and interaction with the community. Therefore, UI/UX design is needed that can increase the effectiveness of information services and strengthen club branding. This research aims to design a UI/UX that reflects the club's visual identity and provides promotional support media. This design is limited to prototyping using Figma without covering technical implementation. This design considers aspects of usability, navigation, visual design, content, compatibility, functionality, accessibility, and interactivity. The results of this design are expected to provide an optimal user experience and become a reference for the development of digital platforms in the field of sports.